(untitled) (The Peerian Journal, 2023)
The purpose of this scientific article is to study and analyze the issues of state financial regulation of entrepreneurial activity in modern conditions. The article considers various aspects of financial regulation, such as taxation, financial support, budget planning and control. The main attention is paid to the analysis of the effectiveness and efficiency of existing mechanisms of financial regulation and their impact on the business environment. The topical issues of state financial regulation of entrepreneurial activity, as well as the conditions that determine the high efficiency and effectiveness of the financial regulators used in the development of small business in the Republic of Uzbekistan, were studied.